CAMM Techniques for the Prediction of the Mechanical Properties of Tendons and Ligaments Nanostructures. (2005) - Vesentini, Simone; Montevecchi, Franco M.; Redaelli, Alberto
Abstract : Theoretical prediction of the mechanical properties of soft tissues usually relies on a top-down approach; that is analysis is gradually refined to observe smaller structures and properties until technical limits are reached. Computer-Assisted Molecular Modeling (CAMM) allows for the reversal of this approach and the performance of bottom-up modeling instead. The wealth of available sequences and structures provides an enormous database for computational efforts to predict structures, simulate docking and folding processes, simulate molecular interactions, and understand them in quantitative energetic terms. Tendons and ligaments can be considered an ideal arena due to their well defined and highly organized architecture which involves not only the main structural constituent, the collagen molecule, but also other important molecular "actors" such as proteoglycans and glycosaminoglycans. In this ideal arena each structure is well organized and recognizable, and using the molecular modeling tool it is possible to evaluate their mutual interactions and to characterize their mechanical function. Knowledge of these relationships can be useful in understanding connective tissue performance as a result of the cooperation and mutual interaction between different biological structures at the nanoscale.